A utilização do processo micro learning na educação profissional e tecnológica - Oliveira, Jaime Gabriel Mendonça de (2022)
This Dissertation is entitled “The Use of the Micro Learning Process in Professional and Technological Education (EPT)” and was prepared in the Postgraduate Program in Professional and Technological Education of the Industrial Technical College of Santa Maria, Federal University of Santa Maria. Nowadays, the educational process goes through several advances of a technical and, above all, technological nature. Attention and focus are on quick and easily accessible information such as that obtained from cell phones. The trend is that the Micro Learning process is used more frequently in Education. Correct use can impact teaching, making it faster and optimizing teacher and student time. This process is related to the research line Innovation for Vocational and Technological Education. In order to update the academic community, the Micro Learning teaching process was researched, as well as its use in EPT, offering subsidies for those who opt for this teaching process. The methodology used was a case study, seeking solutions to the problem presented, in addition to being an innovative process, there is little material in Portuguese, a fact that the case study clarify, offering new contributions. Through the case study, it was possible to resolve doubts and point out possible answers, verify in loco the construction and operation of Micro Learning. For data collection, the selected audiences were teachers and students from the National Service for Commercial Learning, the Municipal School of Industrial Learning and the NPOR Pq R Mnt/3. After collecting and analyzing the data, the expected result will be to know the applicability of the aforementioned teaching process, as well as to know the reality of the “knowledge pills” and their effectiveness. Evaluate the impact of its use and finally develop an applicability guide.